DAMPAK PENDIDIKAN POLITIK TERHADAP PARTISIPASI PEMILIH PEMULA DALAM PEMILU TAHUN 2024 DI NAGARI SINGKARAK KABUPATEN SOLOK DITINJAU DARI PERSPEKTIF FIQIH SIYASAH - oktarina, Soraya (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
Community participation is an important factor in holding elections. Various efforts continue to be made to increase political participation in elections, one of which is through political education programs. The most strategic political education target is the group of beginner voters as potential voters. In Singkarak the level of community political participation reached 70.90%. with a percentage of 15% being the votes of first-time voters. The research method used is a field research method with a qualitative descriptive method. The aim of the research is to see whether the rate of political participation in Nagari Singkarak is caused by efforts to increase political education. The research results show that political education has an impact on voter participation in elections. In Nagari Singkarak, novice voters admitted that they received political education through the formal education route they took. Apart from that, political education is also obtained by novice voters through political socialization activities carried out by a number of political actors in Nagari Singkarak, starting from the KPU, political parties, community organizations, community institutions, families and mass media. Meanwhile, according to Siyasah Fiqh, appointing an imam (leader) is obligatory, the obligatory status is fardhu kifayah. So if someone does not play a role in choosing a leader, it means that he is not carrying out what has been ordered by Islamic law)